2016
DOI: 10.1142/s0129065716500490
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Narrowband High Frequency Oscillations from Asynchronous, Uncoupled Neural Firing

Abstract: Previous experimental studies have demonstrated the emergence of narrowband local field potential oscillations during epileptic seizures in which the underlying neural activity appears to be completely asynchronous. We derive a mathematical model explaining how this counterintuitive phenomenon may occur, showing that a population of independent, completely asynchronous neurons may produce narrowband oscillations if each neuron fires quasi-periodically, without requiring any intrinsic oscillatory cells or feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…However, recent work has shown that HFOs can be generated even in the absence of any network connectivity. 26 These results were recently proven analytically 15 , and though they may seem counterintuitive to the neuroscience and HFO community, they are a well-known phenomenon in complex dynamics. Essentially, a synchronous discharge from an ensemble of cells (which results in a local field potential) does not require any network synchrony or coupling at all, only that the neurons be actively firing at similar frequencies (Fig.…”
Section: Cellular Mechanisms Of Epileptic Hfosmentioning
confidence: 96%
See 1 more Smart Citation
“…However, recent work has shown that HFOs can be generated even in the absence of any network connectivity. 26 These results were recently proven analytically 15 , and though they may seem counterintuitive to the neuroscience and HFO community, they are a well-known phenomenon in complex dynamics. Essentially, a synchronous discharge from an ensemble of cells (which results in a local field potential) does not require any network synchrony or coupling at all, only that the neurons be actively firing at similar frequencies (Fig.…”
Section: Cellular Mechanisms Of Epileptic Hfosmentioning
confidence: 96%
“…1). 10,[13][14][15][16] Synchronization of fast firing within the population of interconnected neurons leads to the formation of an episode of high-frequency population spikes, which is extracellularly recorded as an HFO event ( Fig. 1A,B).…”
Section: Cellular Mechanisms Of Epileptic Hfosmentioning
confidence: 99%
“…The mechanisms producing this fast activity are intriguing, as they appear to require fast firing of many action potentials, indicating a highly active local network (Bragin, et al 2011;Fink, et al 2015;Foffani, et al 2007;Ibarz, et al 2010;Shamas, et al 2018). However, it is not necessary for these phenomena to produce a true coherent oscillation, as the firing cells do not have to be synchronized (Fink, et al 2015;Gliske, et al 2017;Jiruska, et al 2010;Shamas, et al 2018). In terms of detection algorithms, this means that HFOs that are potentially epileptic may have broadband frequency content extending to at least 500 Hz (Blanco, et al 2011;Blanco, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…E) . It is believed that FRs are generated by the out‐of‐phase action potential firing of small neuronal populations, each generating spikes at a much lower frequency . This out‐of‐phase firing then results in a multiplication of the frequency, which in extracellular recording manifests as an oscillation in the FR band.…”
Section: In Vitro Activity With Relevance To Human Epilepsymentioning
confidence: 99%